MENGGALI SEJARAH KONGCO DI PURA BATUR SEBAGAI JEMBATAN TOLERANSI DALAM WUJUD MENCEGAH GEJOLAK MULTIKULTURAL DI BALI - Ade Juliasari Artaningsih (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The existence of various temples in Bali as places of worship for Hinduism is very sacred, one of the temples in Bali which is located in Kintamani District is Ulun Danu Batur Temple. This temple is a symbol of cultural acculturation that reflects tolerance between religious believers. Inside Batur Temple there is a Kongco which is a place of Buddhist worship. The existence of this Kongco originates from the marriage of the Balinese King Jaya Pangus to the Chinese Princess, Kang Cing Wie. Thus creating cultural acculturation between Hindu and Buddhist cultures in Bali. The aim of this research is to identify the existence of Kongco in Ulun Danu Batur Temple as a symbol of cultural acculturation and its function in creating tolerance between religious believers in a multicultural country. This type of research is bibliography, the data collected in this research are two types of data, namely primary data and secondary data. Data obtained from library research (library research). The data collection technique used by this researcher is library research. The research results showed that through various religious ceremonies involving both religious communities, such as Chinese New Year and Pujawali celebrations, the community shows mutual respect between religious communities as one of the launches of multicultural values in Indonesia.